Cutaneous manifestations of primary immunodeficiency diseases in children - Moin, Athar; Farhoudi, Abolhassan; Moin, Mostafa; Pourpak, Zahra; Bazargan, Nasrin (Iranian Journal of Allergy, Asthma and Immunology, 2006)
Primary immunodeficiency diseases (PIDs) are rare but include severe conditions found predominantly in children, Most PIDs have cutaneous manifestations that may be important as early diagnostic features. The purpose of this study was to determine the frequency and nature of cutaneous alterations associated with PIDs. This article is a cross-sectional study at the department of allergy and clinical immunology of children's medical center conducted between December 5, 2001 and April 20, 2002. The subjects included pediatric patients with a diagnosis of PID and dermatological diagnoses were made by a dermatologist. Two hundred and ten patients were studied They consisted of 68 cases of humoral deficiency, 22 cases of cellular and combined deficiencies, 57 cases of phagocytic defects and 63 cases of other PIDs. In 67 cases (31.8%) the cutaneous alterations preceded and were the basis for clinical immunological diagnosis. Overall cutaneous alterations were infections in 99 cases and eczematous dermatitis in 27 cases. Our findings support the results of other studies that most PIDs have cutaneous features which being their typical aspects are highly suggestive for the diagnosis of PIDs.